2012
DOI: 10.1007/s10995-011-0929-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Tobacco Use Among Middle School Students in Saudi Arabia

Abstract: A rapid rise in the number of tobacco users in Saudi Arabia has occurred in the past decade, particularly among the youth. This study identified socio-cultural determinants of tobacco use and explored possible approaches to prevent adolescents' tobacco use in Saudi Arabia. A cross-sectional survey was administered using a self-administered questionnaire for collecting information on risk and protective factors for tobacco use among middle school students. School selection was stratified by region, gender, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…30 Study of Park HK et al (2012) on middle school students in Saudi Arabia had also found similar risk factors affecting tobacco use as found in our study such as perceptions; family, friend, teacher; pressure to use tobacco from friend and; easy access to tobacco to adolescents. 31 The clear social influences and attitudes towards tobacco use and religious beliefs and access to tobacco products were significantly associated with attitudes towards tobacco use and future intention of use in study of Park HK et al (2012) 31 as similar to given findings of our study. We also suggest protective factors for tobacco use such as parents' help; support from family, friends, and teachers; accessibility to tobacco; school& college performance and family income, father's education, and district of residence as similar to Study of Park HK et al (2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…30 Study of Park HK et al (2012) on middle school students in Saudi Arabia had also found similar risk factors affecting tobacco use as found in our study such as perceptions; family, friend, teacher; pressure to use tobacco from friend and; easy access to tobacco to adolescents. 31 The clear social influences and attitudes towards tobacco use and religious beliefs and access to tobacco products were significantly associated with attitudes towards tobacco use and future intention of use in study of Park HK et al (2012) 31 as similar to given findings of our study. We also suggest protective factors for tobacco use such as parents' help; support from family, friends, and teachers; accessibility to tobacco; school& college performance and family income, father's education, and district of residence as similar to Study of Park HK et al (2012).…”
Section: Discussionsupporting
confidence: 90%
“…We also suggest protective factors for tobacco use such as parents' help; support from family, friends, and teachers; accessibility to tobacco; school& college performance and family income, father's education, and district of residence as similar to Study of Park HK et al (2012). 31…”
Section: Discussionmentioning
confidence: 99%
“…[14] The factors that lead adolescents to start smoking include advertising of cigarettes, [15] stress, low self-esteem, poor academic performance, and occurrence of smoking among parents and other family members, friends, and staff at school. [16,17] Moreover, research indicates that initiation of smoking is associated with the perception of risks and benefits of smoking [18] It was found that adolescents with low perception about the long term risks related to smoking were 3.64 times more likely to smoke compared with those who had high perception of smoking related risks. [19] However, the question that whether the awareness about the adverse effects of smoking on oral health has any influence on smoking behaviors among schoolchildren was unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The odds of smoking among females was .08 times which is less than the odds of smoking among males. A study among middle school students conducted in Jeddah, Saudi Arabia, also revealed that gender had been associated with students' attitudes and social in uences towards tobacco consumption (Park et al 2012). Similar ndings were reported in Jeddah among middle school students (Al , and in Riyadh among adolescents (Al-Makadma et al 2015).…”
Section: Discussionmentioning
confidence: 51%